2018
DOI: 10.1016/j.exer.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Collagen fiber crimping following in vivo UVA-induced corneal crosslinking

Abstract: The purpose of this study was to measure collagen fiber crimping (CFC) using nonlinear optical imaging of second harmonic generated (SHG) signals to determine the effects of UVA-riboflavin induced corneal collagen crosslinking (UVA CXL) on collagen structure. Two groups, four rabbits each, were treated in the right eye with standard UVA CXL. In vivo confocal microscopy was performed at 1, 2, and 4 weeks after treatment for the first group and up to three months for the second group to measure epithelial/stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
(95 reference statements)
0
24
1
Order By: Relevance
“…Several studies have shown that some microstructural changes occur after CXL in eyes with keratoconus [16][17][18][19][20]. These microstructural changes allow the anterior corneal stroma (300 µm) to stiffen after surgery, which is related to a crosslinking of collagen fibers [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that some microstructural changes occur after CXL in eyes with keratoconus [16][17][18][19][20]. These microstructural changes allow the anterior corneal stroma (300 µm) to stiffen after surgery, which is related to a crosslinking of collagen fibers [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that the diameter of collagen fibrils and interfibrillar spacing after CXL significantly increase compared to those in untreated keratoconus corneas, whereas the proteoglycan area is significantly smaller [16]. Collagen crimping is also reduced by approximately 1%, possibly due to the shortening of the collagen fibers over the crosslinked region of the cornea [20]. All these modifications are associated with a complete loss of the sub-basal nerve plexus and anterior stromal keratocytes during the early postoperative period, with near-complete regeneration by 12 months postoperatively [18].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 64 ex vivo, intact rabbit eyes were shipped overnight (Pel-Freez, Rogers, AR) and prepared for use upon arrival as previously reported. 5,6,35 Briefly, they were rinsed in phenol-free, low-glucose, Dulbecco's modified Eagle's medium (Sigma Aldrich, St. Louis, MO), inspected for epithelial damage using Lissamine green staining (10 mg/mL in phosphate-buffered saline [PBS]; Sigma Aldrich), and placed in a 37°C, 5% CO 2 humidified incubator for 1 to 2 hours prior to treatment. Eyes showing corneal Lissamine green staining, indicating epithelial damage, were discarded or used as control corneas treated by epithelial debridement.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…Some notable study findings include the study conducted by Wollensak et al, where the rigidity of the cornea was observed to have increased by 328.9% after collagen crosslinking [189] and increased Young’s modulus up to 8 months post-CXL with no significant difference in corneal thickness [190]. The effects of CXL on collagen structure have shown decreased collagen waviness or crimping in the anterior corneal stroma by 1-month post-riboflavin-mediated CXL in a rabbit model [191]. Riboflavin-mediated CXL of the cornea has also been associated with loss of corneal transparency by 1 month, though resolution of the haze is evident by 3 months post-CXL in rabbit models [191].…”
Section: Effects Of Crosslinking On Corneal Structurementioning
confidence: 99%
“…The effects of CXL on collagen structure have shown decreased collagen waviness or crimping in the anterior corneal stroma by 1-month post-riboflavin-mediated CXL in a rabbit model [191]. Riboflavin-mediated CXL of the cornea has also been associated with loss of corneal transparency by 1 month, though resolution of the haze is evident by 3 months post-CXL in rabbit models [191]. In a human clinical trial, the efficacy of CXL determined based on the maximum keratometry in the crosslinked group compared to sham controls showed an improvement in corneal steepening (K max ) by 1.6 diopters with a parallel improvement in visual acuity by at least 1 line (corrected distance visual acuity) at 1-year post-CXL [192].…”
Section: Effects Of Crosslinking On Corneal Structurementioning
confidence: 99%